Seeing Gender in Policing: Uniforms and Perceived Aggression. Issue 5 (3rd September 2021) - Simpson, Rylan; Croft, Alyssa
Abstract: Policing has historically been conceptualized as a masculine and male-dominated profession. As part of the present research, we test two competing hypotheses about the effects of officer gender on citizens' ( N = 251) perceptions of officer aggression. Our results reveal that women are perceived as less aggressive than men when wearing civilian clothes, but similarly aggressive as men when wearing their police uniform. By experimentally testing the salience of policing versus gender cues on judgments of officers, we provide insight into the gendered dynamics of policing and complement existing research in the fields of criminology and psychology.